Magnetic Resonance Imaging-Based Prevalence of Anterolateral Ligament Abnormalities and Associated Injuries in Knees with Acute Anterior Cruciate Ligament Injury - Song, Yoonah; Yang, Jae-Hyuk; Choi, Won Rak; Lee, Jin Kyu (The Journal of Knee Surgery, 2019)
The purpose of this study was to determine and compare the prevalence of anterolateral ligament abnormality and associated injuries among patients with complete and partial anterior cruciate ligament tears. In addition, the prevalence of associated injuries with anterolateral ligament abnormality was further analyzed. Of the 158 patients diagnosed with acute anterior cruciate ligament tear, 82 patients were diagnosed with acute complete anterior cruciate ligament confirmed by magnetic resonance imaging (MRI) and arthroscopic procedures (Group C), and 74 patients were diagnosed with acute partial anterior cruciate ligament tears confirmed by MRI (Group P). The status of the anterolateral ligament, collateral ligaments, menisci, and osseous lesions was assessed. There was a significantly higher prevalence of anterolateral ligament abnormalities in Group C than Group P (36.6 vs. 4.1%, p < 0.001). Medial collateral ligament, lateral collateral ligament, Segond fracture, osseous lesion at the fibular head, lateral tibial plateau, lateral femoral condyle, and medial tibial plateau were significantly associated with anterolateral ligament abnormality. Furthermore, severity of osseous lesion at the lateral tibial plateau, lateral femoral condyle, and medial tibial plateau was significantly associated (with linear correlation) with anterolateral ligament abnormality. The prevalence of anterolateral ligament abnormality was significantly higher in patients with complete anterior cruciate ligament tear (36.6%) than those with partial anterior cruciate ligament tear (4.1%), but with noticeable prevalence of anterolateral ligament abnormality in the partial anterior cruciate ligament tear group. Associated lesions significant to anterolateral ligament abnormality were tears in both collateral ligaments, lateral-sided osseous lesions, and osseous lesion of the medial tibial plateau.
Keywords: magnetic resonance imaging; anterolateral ligament; anterior cruciate ligament